Diary of a wimpy kid the meltdown - Kinney, Jeff (Waterville, Maine Amulet Books, 2018)
When snow closes Greg Heffley's middle school, he and his best friend, Rowley Jefferson, face a fight for survival as warring gangs turn the neighborhood into a wintry battlefield
English stories
"Thorndike Press® Large Print The Literacy Bridge"
1
Keywords: Large type books; Humorous stories; JUVENILE FICTION / Comics & Graphic Novels / General; Best friends -- Fiction; Diaries -- Fiction; Friendship -- Fiction; JUVENILE FICTION / Humorous Stories; Large type books; Snow -- Fiction; Winter -- Fiction